3D printing by additive manufacture of hydrogel containing caffeic acid - Moraes Segundo, João de Deus Pereira de; Corzo, Ingri Julieth Mancilla; Moraes, Maria Oneide Silva de; da Fonsêca, Jéssica Heline Lopes; Tavares, Rêner Pontes; Paula, Brenda Silva de; dos Santos, Gedeandro Gonçalves; Almeida Mendes, Sthefany Ananda Bruna; Levy, Catarina Barbosa; Farias, Taisa Lorene Sampaio; Silva, Rudyere Nascimento; d’Ávila, Marcos Akira (International Journal of Advanced Engineering Research and Science, 2021)
In this work, 3D extrusion-based printing head was used to produce 3D geometry of hydrogel containing caffeic acid (CA). The hydrogel was prepared with 10wt.% polyvinylpyrrolidone (PVP) and 3wt.% sodium carboxymethylcellulose (CMC) using deionized water as solvent (PVP-CMC hydrogel), likewise the PVP-CMC hydrogel containing CA was prepared but was added 2wt.% CA (PVP-CA-CMC hydrogel). The rheological properties of the hydrogels were obtained using a modular rheometer with plate-plate geometry. The PVP-CMC hydrogel presented shear-thinning flow behavior and the adding of CA did not affect its rheological behavior. The power-law model described the shear-thinning curves of the hydrogels. Frequency sweep tests demonstrated that the PVP-CMC and PVP-CA-CMC hydrogels presented a physical gelation characteristic of the solid behaviors. The IR spectroscopy chemically characterized the hydrogel, indicating by carbonyl peaks a good intermolecular interaction between the functional groups. Therefore, we demonstrated the printing capacity of the PVP-CMC inks with caffeic acid, which makes it interesting to additive manufacture field.